The Price and Volume Effect of Single-Stock Futures Trading on the Pakistani stock market - Adil Awan; Syed M. Amir Shah (The Lahore Journal of Business)
The advent of single-stock futures (SSFs) provides an opportunity to investigate the company-wide impact of futures trading rather than the marketwide response captured through index futures contracts. This study analyzes the price and volume effect of SSFs on the underlying spot market based on a sample of 26 Pakistani firms. The dataset used includes one-year pre- and post-event data on closing prices and trading volumes. We conduct an event study in which the abnormal returns of individual companies and average abnormal returns reveal that futures trading has very little impact on the underlying spot returns. The cumulative abnormal returns show that statistically significant positive abnormal returns are experienced after SSF trading but with negative returns in the preevent period. We compare pre- and post-event average normalized volumes using the t-test and dummy variable regression; the trend coefficients show a general decrease in trading volume. Consequently, there is an increase in returns and decrease in trading volume post-SSF trading in the Pakistani market.